Nautical Tourism in Croatia and in Portugal in the Late 2010’s - Kovačić, Mirjana (2018)
Croatia is one of the well - known Mediterranean destinations for nautical tourism which full development potential is waiting to be used. Cultural attractions, indented coastline, numerous islands, climatic and other advantages are not enough. Croatia needs new infra- and supra-structures, which are reflected through investments in new marinas, anchorages and other facilities. Portugal is an Atlantic country, but with a Mediterranean culture due to its proximity and (potentially) benefiting from its extensive shoreline, two archipelagos, and being located in a geographical position where thousands of yachts pass by each year. The article aims to analyse the accommodation capacities of nautical tourism ports in Croatia and in Portugal. The authors have given an overview of the current situation with an emphasis on the differences and possibilities. The purpose of this article is to analyse the legal objective of nautical tourism and the growing need for accommodation capacities in ports of nautical tourism in both countries. The authors have carried out the research and have analysed data from different years and regions. Although more in Croatia, nautical tourism is a significant part of the national economy in both countries with a strong incentive on the local community. The special goal of this paper is to research into and analyse the economic and ecological impact of nautical tourism through ports of nautical tourism and with a special emphasis on marinas. The result obtained and the critical overview has been presented as one of the important contributions of this paper.